1990
DOI: 10.1021/jm00167a031
|View full text |Cite
|
Sign up to set email alerts
|

N-(3-[18F]Fluoropropyl)-N-nordiprenorphine: synthesis and characterization of a new agent for imaging opioid receptors with positron emission tomography

Abstract: A series of N-fluoroalkyl (1-5) and N-alkyl (6-8) analogues of the high-affinity opioid receptor antagonist diprenorphine (9) has been synthesized and evaluated with in vitro binding assays. Three of the N-fluoroalkyl compounds were prepared with the positron-emitting radionuclide 18F (1a, 2a, 5a), and their biodistribution was determined in rats. Compounds 2a and 5a were made by using a two-step labeling procedure, [18F]fluoride displacement of an iodoalkyl triflate followed by N-alkylation, that required 2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 2 publications
1
20
0
Order By: Relevance
“…Although this fluoroalkylation decreased the in vitro affinity of the analog, in vivo studies showed some retention of specific binding. Additional analogs have been described by Chesis et al . Their in vitro and in vivo results were quite similar to the earlier paper; however, there appears to have been no subsequent in vivo PET publications for these analogs.…”
Section: Radiotracers That Bind To Multiple Subtypessupporting
confidence: 74%
“…Although this fluoroalkylation decreased the in vitro affinity of the analog, in vivo studies showed some retention of specific binding. Additional analogs have been described by Chesis et al . Their in vitro and in vivo results were quite similar to the earlier paper; however, there appears to have been no subsequent in vivo PET publications for these analogs.…”
Section: Radiotracers That Bind To Multiple Subtypessupporting
confidence: 74%
“…The use of the iodoallyl prosthetic group for incorporation of radioiodine is essential because direct iodination of the phenolic ring of morphinans such as DPN leads to a severe loss in opioid receptor binding potency (Casy and Parfitt, 1986). Similarly, modification at the N-position by iodoalkyl (Chesis et al, 1990) or iodoallyl moieties is not well-tolerated. By contrast, high affinity is maintained for morphinans substituted with bulky groups at the C6-position (Hazum et al, 1982;Kolb et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Compartmental modeling and reference tissue methods generate quantitative parametric maps of [ 18 F]fluoroethyldiprenorphine binding in human brain [149], the tracer is in use for studies of nociceptive pathways [150], and single-bolus protocols are under development to allow measurements of endogenous opioid release in a single imaging session [151]. Properties for PET are superior to those of previously studied ligands having N-[ 18 F]fluoroalkyl groups in place of the cyclopropylmethyl [152,153].…”
Section: [ 11 C]diprenorphine [ 18 F]cyclofoxy and Other Ligands Formentioning
confidence: 99%